Analytical solution for pressure-controlled elliptical cavity expansion in elastic-perfectly plastic soil. Issue 2 (2nd June 2014) - ,; ,; ,; Cao, Z.
Abstract : This note presents a new pressure-controlled elliptical cavity expansion model for elastic-perfectly plastic soil. The model accounts for the non-asymmetric characteristics of elliptical cavity expansion, which differ from conventional asymmetric cylindrical cavity expansion. A closed-form solution for the pressure-expansion relationship is used to predict the uplift capacity of strip anchors in undrained clay. Theoretical variations of the strip anchor breakout factor are compared with conventional cylindrical cavity expansion theory and laboratory test results and upper and lower bound finite element limit analysis solutions from the literature. The results show that a pressure-controlled elliptical cavity expansion model can predict the uplift capacity of strip anchors in undrained claymore accurately than the conventional cavity expansion method at larger embedment depths (H/B.3). The proposed solution improves on the conventional cavity expansion theory and provides a new method for solving the non-asymmetric cavity expansion problem.